Fully distributed certificate authority based on polynomial over elliptic curve for MANET - Ahmad Alomari (International Journal of Networked and Distributed Computing (IJNDC), 2014)
A mobile ad hoc network (MANET) is a wireless communication network, which does not rely on any centralized management or a pre-existing infrastructure. Various certificate authorities (CAs) distributed over the network, each with a periodically updated share of the secrete key, is usually adopted. Elliptic Curve Cryptography (ECC) is a cryptographic technique prominent suited for small devices, like those used in wireless communications, and is gaining momentum. The main advantage of ECC versus RSA is that for the same level of security it requires a much sorter key length. The purpose of this work is to design and implement a fully certificate authority based on polynomial over elliptic curve, based on trust graphs and threshold cryptography, which though has better cryptography in nature. The security is based on the elliptic curve discrete logarithm problem.